Indoor Lighting Assessment in the CeDS Academic Office Space - Mohamad Rizuan, Muhammad Afiq Iskandar; Ismayazan, Muhammad Danish Ilman; Abdul Rahman, Abid Naufal Bazli; Abd Kadir, Aslila (Multidisciplinary Applied Research and Innovation, 2026)
This study focuses on evaluating the lighting quality in the CeDS Administration Office at Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh by measuring current lighting levels, comparing them with the recommended MS1525:2014 standards, and assessing staff satisfaction with existing lighting conditions. Surveys will be used to gather data on occupants’ satisfaction, covering aspects such as visual comfort, glare, and the impact of lighting on productivity and health, while lighting measurements will be taken at different times of the day to capture variations in conditions. The collected data will help determine compliance with Malaysian lighting standards and highlight areas needing improvement. Findings are expected to identify zones with insufficient or excessive lighting that may affect employee satisfaction and performance, offering a deeper understanding of the influence of lighting on workplace comfort and efficiency. Ultimately, the study aims to provide actionable recommendations for optimizing lighting in the CeDS Administration Office, enhancing employee well-being, reducing health risks such as eyestrain and fatigue, and contributing to the creation of a healthier, more productive office environment.